Renormalization group evolution for the ΔS=1 effective Hamiltonian with Nf=2+1 - Lee, Weonjong. (2013)
We discuss the renormalization group (RG) evolution for the ΔS=1 operators in unquenched QCD with N f =3 (m u =m d =m s ) or, more generally, N f =2+1 (m u =m d ≠m s ) flavors. In particular, we focus on the specific problem of how to treat the singularities which show up only for N f =3 or N f =2+1 in the original solution of Buras et al. for the RG evolution matrix at next-to-leading order. On top of the original treatment of Buras et al., we use a new method of analytic continuation to obtain the correct solution in this case. It is free of singularities and can therefore be used in numerical analysis of data sets calculated in lattice QCD.